A kinetic investigation of chromium - Kocaoba, S; Akcin, G (KLUWER ACADEMIC PUBL, 2003)
A kinetic investigation was performed with an ion exchange resin for chromium. A chelating cation exchange resin ( Amberlite IRC 718) was used for removal and recovery of chromium. The effect of concentration, resin amount, particle size and stirring speed on kinetics were investigated. The metal concentration range studied was between 5 to 160 mg L-1, the resin amount range was between 5 to 20 mg, the particle size range was between 0.35 to 1.8 mm and the stirring speed range was between 1000 to 3500 rpm. Kinetic studies were done using a Kressman-Kitchener stirrer reactor system and the results were compared with existing kinetic models. Two models; Nernst-Plank film diffusion control model (fdc) and solid phase diffusion control model (pdc) were identified and the dependence of the rate on parameters, such as solution concentration, particle size, resin amount, stirring speed, etc., was examined for each of them. As a result, interpretation of these data showed that the system is probably controlled both film and particle diffusion.
Keywords: kinetics; chelating weakly acidic exchange resin; chromium; Kressman-Kitchener stirrer reactor; ION-EXCHANGERS; REMOVAL; Chemistry; Engineering